2021
DOI: 10.1007/s12630-021-01928-0
|View full text |Cite
|
Sign up to set email alerts
|

Family veto in organ donation: the experiences of Organ and Tissue Donation Coordinators in Ontario

Abstract: Purpose In Ontario, an individual's registered wish for organ donation is legally valid consent following death. Family veto occurs when the deceased donor's substitute decision-maker (SDM) overrides this consent to donate, evoking a legal and ethical conflict. The objective of this study was to examine the experiences of Organ and Tissue Donation Coordinators (OTDCs) working with SDMs who vetoed a deceased donor's consent for organ donation. Methods Qualitative focus groups were conducted with ten OTDCs in On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
7
0
2
Order By: Relevance
“…Our study was similar to Anthony, [ 20 ] who found that the support of other family members resulted in a significant difference in the willingness to sign the COD. These outcomes show that disagreements among family members often cause a failure to solicit organ donation.…”
Section: Discussionsupporting
confidence: 89%
“…Our study was similar to Anthony, [ 20 ] who found that the support of other family members resulted in a significant difference in the willingness to sign the COD. These outcomes show that disagreements among family members often cause a failure to solicit organ donation.…”
Section: Discussionsupporting
confidence: 89%
“…As clinicians and a clinical ethicist with an academic and clinical interest in organ donation and transplantation, we were intrigued by the article written by Anthony et al, in this issue of the Journal, entitled ''Family veto in organ donation: the experiences of organ and tissue donation coordinators in Ontario''. 1 This research team conducted semi-structured interviews with Ontario Organ and Tissue Donation Coordinators (OTDCs) to better understand their experiences and perspectives regarding family vetoes for organ donation. Although only ten OTDCs participated in the study, the research team ensured the OTDCs were experienced at their role, and that there was a diversity of age and practice location.…”
mentioning
confidence: 99%
“…As the authors correctly state: ''SDMs have no legal authority to withhold organ donation authorization if the deceased donor had previously consented''. 1 It is commendable that well-meaning healthcare team members go to great lengths to comfort families at their time of grief. Indeed, some OTDCs in the study recognized the occasional ''acceptable veto.''…”
mentioning
confidence: 99%
See 2 more Smart Citations